Financial liberalization in a small open economy - Jürgen von Hagen; Haiping Zhang (Center for Economic Studies and ifo Institute (CESifo), 2006)
We analyze the long-run and short-run implications of financial liberalization in a small open economy. Our main results are as follows. First, whether financial deregulation in one sector can improve production efficiency may depend on financial regulation in other sectors. Second, financial liberalization may have opposite welfare implications to domestic agents with different productivity in the long run. Third, although some domestic agents lose in the long run, they benefit from financial liberalization during the transitional process of deregulation. Finally, a gradual implementation helps achieve a smooth transition.
Keywords: E32; E44; F34; F41; 330; Kapitalmarktliberalisierung; Kleines-offenes-Land; Wirtschaftspolitische Wirkungsanalyse; Theorie